Analysis of Determinants: Indonesian Case - Sari, Vita Kartika (Buletin Ilmiah Litbang Perdagangan, 2024)
Exports directly impact national income, which will also have implications for increasing levels of productivity, innovation, and technology transfer. The urgency of exports from an open economic perspective is to increase the capacity for economic growth. Unfortunately, various factors often hinder export performance, disrupting the potential benefits. The main objective of this study is to analyze the impact of macroeconomic variables, namely the exchange rate, foreign direct investment (FDI), Gross Domestic Product (GDP) per capita, and inflation on Indonesian exports in the period 1970-2022. This research uses time series data with the Autoregressive Distributed Lag-Error Correction Model (ARDL-ECM) method. The findings of the analysis show that the exchange rate, FDI, GDP per capita, and inflation have a positive and significant effect on exports in the long term. Therefore, if the Indonesian government wants to maintain its trade balance, it is recommended to keep a floating and controlled exchange rate policy and coordinate pro-export-oriented investment policies.